ANALYSIS ON Alu-I GROWTH HORMONE (GHAlu-I) GENE IN BALI CATTLE - Jakaria, J.; Noor, R.R. (Diponegoro University, 2011)
The research was conducted to identify Alu-I locus of growth hormone (GH) gene in Bali cattle byusing 232 blood samples collected from Bali and Lombok islands. PCR-RFLP and sequencing methodswere used to detect the polymorphism and nucleotide sequence at Alu-I locus of GH gene. The resultshowed that Bali cattle from Bali island has one genotype (LL genotype), whereas Bali cattle originatingfrom Lombok island has two genotypes, namely LL and VV genotypes, respectively. The L and V allelefrequencies from Bali and Lombok islands were 1.00 and 0.00; 0.99 and 0.01, respectively. Thesequencing result of Bali cattle LL genotype showed an AGCT sequence of enzyme Alu-I restriction site.Based on polymorphic informative content (PIC) value, it can be concluded that Alu-I locus of Balicattle from Bali and Lombok islands were monomorphic and polymorphic, respectively.